The concept of Ũtugi within the HIV and AIDS pandemic : a pastoral assessment of the ecclesial praxis of the Anglican Church in Kenya - Murage, Josiah Kinyua (Stellenbosch : Stellenbosch University, 2011)
Thesis (DTh)--Stellenbosch University, 2011.